2019
DOI: 10.12968/bjca.2019.14.2.72
|View full text |Cite
|
Sign up to set email alerts
|

Does electronic decision support influence advanced life support in simulated cardiac arrest?

Abstract: In-hospital Cardiac arrest is common but despite mandatory resuscitation training for staff, the survival rates vary considerably. The reason for such variation is unclear but may relate to a number of human factors. Decision support systems and tools have been suggested as a means of reducing human errors and improve patient outcome. In this proof of concept study, we tested the use of such a device in a simulated environment Methods The aims of this study were firstly, to investigate if the introduction of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Of the 4224 screened studies, 16 met our inclusion criteria: 14 adult CA studies [32][33][34][35][36][48][49][50][51][52][53][54][55][56] (for a total of 688 scenarios) and two paediatric CA studies [30,31] (for a total of 46 scenarios). The PRISMA flow chart for the study selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 4224 screened studies, 16 met our inclusion criteria: 14 adult CA studies [32][33][34][35][36][48][49][50][51][52][53][54][55][56] (for a total of 688 scenarios) and two paediatric CA studies [30,31] (for a total of 46 scenarios). The PRISMA flow chart for the study selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The articles were published between 1995 and 2021, with nine (64%) published in the past three years [33,34,48,49,[52][53][54][55][56]. Thirteen studies were RCTs: seven with a crossover design [35,36,49,51,[54][55][56], five with a two-arm parallel design [32,34,48,50,53], and one with a three-arm parallel design [33].…”
Section: Studies Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations